1999
DOI: 10.1002/(sici)1521-4141(199909)29:09<2695::aid-immu2695>3.0.co;2-q
|View full text |Cite
|
Sign up to set email alerts
|

The monoclonal antibody DCGM4 recognizes Langerin, a protein specific of Langerhans cells, and is rapidly internalized from the cell surface

Abstract: We generated monoclonal antibody (mAb) DCGM4 by immunization with human dendritic cells (DC) from CD34+ progenitors cultured with granulocyte‐macrophage colony‐stimulating factor and TNF‐α. mAb DCGM4 was selected for its reactivity with a cell surface epitope present only on a subset of DC. Reactivity was strongly enhanced by the Langerhans cell (LC) differentiation factor TGF‐β and down‐regulated by CD40 ligation. mAb DCGM4 selectively stained LC, hence we propose that the antigen be termed Langerin. mAb DCGM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
151
0
1

Year Published

2002
2002
2012
2012

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 245 publications
(165 citation statements)
references
References 25 publications
12
151
0
1
Order By: Relevance
“…In agreement with previous reports, Langerin expression could not be detected in tonsil ( Fig. 1) (11).…”
Section: Dc-sign and The Other C-type Lectins Langerin Mr And Dec-2supporting
confidence: 93%
See 1 more Smart Citation
“…In agreement with previous reports, Langerin expression could not be detected in tonsil ( Fig. 1) (11).…”
Section: Dc-sign and The Other C-type Lectins Langerin Mr And Dec-2supporting
confidence: 93%
“…However, the number of CRDs present in these lectins differs and the complexity of the mannose groups that they recognize is distinct (9,10). Langerin contains a single CRD and functions on skin epidermal Langerhans cells (LCs) as an endocytic receptor that is associated with and induces formation of Birbeck granules (11,12). The MR, highly expressed on immature DCs and macrophages, has eight potential CRDs, of which two were shown to be functional for binding end-standing mannose groups on a variety of pathogens and Ags, illustrating its role in innate immunity (13,14).…”
Section: The Dendritic Cell-specific Adhesion Receptor Dc-sign Internmentioning
confidence: 99%
“…Hence, we next investigated whether Langerin, which is already known to endocytose in LCs (Valladeau et al, 1999(Valladeau et al, , 2000, cycles through the early endosomal pathway in a similar manner to CD1a molecules.…”
Section: Molecular Biology Of the Cell 320mentioning
confidence: 99%
“…Mouse monoclonal antibodies (mAbs) were as follows: anti-lag (IgG1, recognizing an intracellular epitope of Langerin; kindly provided by Dr. Sadao Imamura, Kyoto University, Sakyo-ku, Kyoto, Japan) (Kashihara et al, 1986;Valladeau et al, 2000), DCGM4 (IgG1, recognizing an extracellular epitope of Langerin; Immunotech, Marseille, France) (Valladeau et al, 1999), L243 (IgG2a, anti-DR␣␤ dimmers; BD Biosciences, San Jose, CA), fluorescein isothiocyanate (FITC)-conjugated H1149 (IgG1, anti-CD1a; BD PharMingen, San Diego, CA), H5C6 (IgG1, anti-CD63; kindly provided by Dr. François Lanza, EFS-Alsace, Strasbourg), tetramethylrhodamine B isothiocyanate (TRITC)-conjugated Phalloidin (Sigma, St. Louis, MO), and H4B4 (IgG1, anti-Lamp-2 [CD107b], BD PharMingen). Rabbit anti-EEA1 antiserum (Simonsen et al, 1998) was a generous gift of Dr. Harald Steinmark, (EMBL, Heidelberg, Germany).…”
Section: Antibodies and Reagentsmentioning
confidence: 99%
“…Recently, the 5 0 untranslated region of DC-STAMP gene was successfully used in lentiviral vectors yielding long-term and cell-selective transgene expression in vivo. 13 In order to develop additional vectors for permissive expression in DCs in vitro and in vivo with protein, the promoters of the murine genes encoding cd11c, dc-sign, 22 dc-stamp 23 and langerin 24 were cloned. We demonstrated that the DNA sequences that we cloned were primarily active in the DC cell lines, D1, and differentiated Raw 264.7 cells.…”
Section: Introductionmentioning
confidence: 99%